Saccular or dissecting aneurysms involving the basilar trunk: Endovascular treatment and clinical outcome. (3rd July 2019) - Cho, Kwang-Chun; Jeon, Pyoung; Kim, Byung Moon; Lim, Soo Mee; Jung, Woo Sang; Kim, Jung-Jae; Suh, Sang Hyun
ABSTRACT: Objectives : Basilar artery trunk aneurysms (BTAs) are a rare pathology and difficult to treat. We present our experience regarding angiographic results and clinical outcomes for 16 BTAs treated by reconstructive endovascular treatment (EVT) using stent or balloon. Methods : Between January 2003 and December 2014, 15 patients (mean age, 58.6 years; 11 males) with 16 BTAs were enrolled. Clinical manifestation, outcomes and procedural complications were evaluated retrospectively, and follow-up angiography was performed 12 and 24 months after procedure. Results : Subarachnoid hemorrhage (SAH) developed in seven aneurysms and nine were found incidentally. In one case, SAH followed by acute infarction on pons. The location of the aneurysms was the pure basilar artery (BA) trunk in 13 and the junction of the BA and the superior cerebellar artery in 3. Reconstructive EVT was technically successful in 15 aneurysms (93.8%) and failed in one due to the difficulty of vascular access. Stent/balloon-assisted coiling was performed in 13 aneurysms and sole stent therapy in two aneurysms. One patient had periprocedural complication of acute in-stent thrombosis. All treated patients had no symptoms with the usual activities except three patients, who died from myocardial infarction, aneurysmal rebleeding, and cerebellar infarction. Angiographic follow-up was performed in nine aneurysms; three aneurysms were recanalized (33.3%) and six aneurysms had no interval change (66.7%). There was no significant event during the follow-up period (mean, 23.5 months). Conclusion : In the treatment of BTAs, reconstructive EVT may provide a feasible and safe option to microsurgery.